2017
DOI: 10.1007/s00440-016-0751-z
|View full text |Cite
|
Sign up to set email alerts
|

Dyson Ferrari–Spohn diffusions and ordered walks under area tilts

Abstract: Abstract. We consider families of non-colliding random walks above a hard wall, which are subject to a self-potential of tilted area type. We view such ensembles as effective models for the level lines of a class of 2 + 1-dimensional discrete-height random surfaces in statistical mechanics. We prove that, under rather general assumptions on the step distribution and on the self-potential, such walks converge, under appropriate rescaling, to non-intersecting Ferrari-Spohn diffusions associated with limiting Stu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 23 publications
(40 reference statements)
1
28
0
Order By: Relevance
“…as L → ∞ converges weakly to the stationary Ferrari-Spohn diffusion, namely the reversible diffusion process on R + with potential given by the logarithm of the Airy function, which was first introduced in [11]. On the other hand, for fixed n, and for λ = 1, the ensemble of random lines described by (1.1) has been analysed in [16], where it is shown that the vector of rescaled trajectories…”
mentioning
confidence: 99%
“…as L → ∞ converges weakly to the stationary Ferrari-Spohn diffusion, namely the reversible diffusion process on R + with potential given by the logarithm of the Airy function, which was first introduced in [11]. On the other hand, for fixed n, and for λ = 1, the ensemble of random lines described by (1.1) has been analysed in [16], where it is shown that the vector of rescaled trajectories…”
mentioning
confidence: 99%
“…As a result of this progress the semicircular case may have lost some of its initial motivation. However, Brownian excursion, conditioned to stay away from a moving wall, continues to attract attention, and it has been recently generalized in several directions [9][10][11][12][13]. 2 Already in their original paper [3] the authors noticed that finer details of their model differ from those of models of the KPZ universality class.…”
mentioning
confidence: 99%
“…Another important difference is that in the SOS model [10] one never sees the top monolayer detached from the rest of them, as in the model we consider. Nevertheless, we believe that in our model with k monolayers the fluctuations of their boundaries in the vicinity of the (vertical) wall are, as in the case of entropic repulsion [11], of the order of N 1/3 , and their behavior is given, after appropriate scaling, by k non-intersecting Ferrari-Spohn diffusions [23], as in [26,29]. See [28] for a review.…”
Section: Introductionmentioning
confidence: 98%